Increasing the incidence of drain‐free day‐case mastectomies with the use of a fibrin tissue sealant; data from a single surgical center in the United Kingdom. Issue 6 (23rd July 2019) - Harrison, Conrad; Remoundos, Dionysios D.; Harvey, Kate L.; Stoker, Gill V.; MacLean, Gael; Adwani, Asha; Roy, Pankaj G.
Abstract: Day‐case mastectomy surgery provides benefits to both patients and hospitals. Key barriers are the use of a drain and the risk of postoperative seroma formation. We introduced the use of a tissue sealant (Artiss) into the surgical site (post‐mastectomy without immediate reconstruction and postaxillary clearance) and evaluated its effect on our practice, particularly day‐case rates. A prospective audit of 177 patients who underwent a simple mastectomy with or without axillary surgery, or axillary node clearance with or without breast‐conserving surgery was conducted at a single surgical center in the UK between November 2015 and November 2016. Artiss was used in all operations and, where appropriate, the drain was omitted to facilitate day‐case surgery. The clinical outcomes were compared between patients undergoing different operations and duration of hospital stay. There was no statistically significant difference between day‐case patients and inpatients in seroma aspiration rates (24.5% and 21.7%, respectively; P  = 0.381) or other complications (22.4% and 16.1%, respectively; P  = 0.106). The day‐case mastectomy rate increased from 3.9% in the first quarter to 45.5% in the final quarter, which was a significant increase reaching well beyond the national target. The use of Artiss enabled us to increase the drain‐free day‐case surgery rates over a 1‐year period, exceeding the 30% target recommended by the British Association of Day Surgery. We did not observe any increase in patient morbidity, and the change was cost‐effective. We have now implemented the routine use of Artiss in women undergoing simple mastectomy with or without axillary surgery and stand‐alone axillary node clearances as part of enhanced recovery clinical pathways.